Discovery of small molecule inhibitors of Plasmodium falciparum apicoplast DNA polymerase - Supreet Kaur; Nicholas S. Nieto; Peter McDonald; Josh R. Beck; Richard B. Honzatko; Anuradha Roy; Scott W. Nelson (Taylor & Francis Group, 2022)
Malaria is caused by infection with protozoan parasites of the Plasmodium genus, which is part of the phylum Apicomplexa. Most organisms in this phylum contain a relic plastid called the apicoplast. The apicoplast genome is replicated by a single DNA polymerase (apPOL), which is an attractive target for anti-malarial drugs. We screened small-molecule libraries (206,504 compounds) using a fluorescence-based high-throughput DNA polymerase assay. Dose/response analysis and counter-screening identified 186 specific apPOL inhibitors. Toxicity screening against human HepaRG human cells removed 84 compounds and the remaining were subjected to parasite killing assays using chloroquine resistant P. falciparum parasites. Nine compounds were potent inhibitors of parasite growth and may serve as lead compounds in efforts to discover novel malaria drugs.